Hazard characterisation for significant mycotoxins in food - Malir, Frantisek; Pickova, Darina; Toman, Jakub; Grosse, Yann; Ostry, Vladimir (Mycotoxin research, 2023)
This review updates the current status of activities related to hazard characterisation for mycotoxins, with special reference to regulatory work accomplished within the European Union. Because the relevant information on these topics is widely scattered in the scientific literature, this review intends to provide a condensed overview on the most pertinent aspects. Human health risk assessment is a procedure to estimate the nature and potential for harmful effects of mycotoxins on human health due to exposure to them via contaminated food. This assessment involves hazard identification, hazard characterisation, exposure assessment, and risk characterisation. Mycotoxins covered in this review are aflatoxins, ochratoxin A, cyclopiazonic acid, citrinin, trichothecenes (deoxynivalenol, nivalenol, T-2, and HT-2 toxins), fumonisins, zearalenone, patulin, and ergot alkaloids. For mycotoxins with clear genotoxic/carcinogenic properties, the focus is on the margin of exposure approach. One of its goals is to document predictive characterisation of the human hazard, based on studies in animals using conditions of low exposure. For the other, non-genotoxic toxins, individual 'no adverse effect levels' have been established, but structural analogues or modified forms may still complicate assessment. During the process of hazard characterisation, each identified effect is assessed for human relevance. The estimation of a 'safe dose' is the hazard characterisation endpoint. The final aim of all of these activities is to establish a system, which is able to minimise and control the risk for the consumer from mycotoxins in food. Ongoing research on mycotoxins constantly comes up with new findings, which may have to be implemented into this system.
Keywords: Mycotoxins; Ergot Alkaloids; Aflatoxins; patulin; zearalenon; Hazard characterisation; aflatoxiny; Health risk assessment; fumonisiny; kontaminace potravin; mykotoxiny; Fumonisins; Patulin; Zearalenone; zvířata; Humans; námelové alkaloidy; Food; Food Contamination; Total diet study; lidé; Animals